Proteomic applications for studies of bull fertility - Viana, Arabela Guedes de Azevedo (2022)
During spermatogenesis, the immature spermatozoon undergoes a series of morphological changes, and the nucleus is highly condensed to protect the DNA. Thus, the apparently transcriptionally silent sperm exclusively depends on the extracellular factors for survival and functionality. The seminal plasma (SP) is a fluid produced by accessory sexual glands, epididymides, and testes, and plays crucial roles in the ejaculated sperm. Understanding the complexity of the SP proteins is still a challenge and proteomic approaches have been widely used to uncover SP proteins and, consequently, potential protein biomarkers of bull fertility. To verify the state of the art of the SP proteome and its relationship with sperm fertility in bulls, we applied an extensive and systematic literature search to select 71 and 29 studies for systematic review and meta-analysis research, respectively. Qualitatively, the exposure to a single protein, such as osteopontin (OPN), binder of sperm proteins (BSPs), and heparin- binding proteins (HBPs), positively associates with sperm motility, capacitation, and fertilizing ability. Quantitatively, our meta-analysis revealed that seminal proteins ameliorate sperm parameters. BSPs and beta-defensin 126 highly favored sperm protection when cells were collected from the epididymis by retrograde flux and analyzed under room temperature conditions. Total SP proteins improved the motility and quality of Bos taurus sperm collected by artificial vagina, mainly in the presence of HBPs. Due to the diversity of methodologies applied in the eligible studies, the translational aspects of SP research should be taken into consideration to precisely define how seminal proteins can be harnessed to advance reproductive biotechnology. Then, we suggested that future studies should evaluate intact proteins to ascertain their biological functions. To address this question, we evaluated the associations between seminal proteoforms in bulls with contrasting freezability statuses. We employed top-down mass spectrometry to generate sperm and seminal plasma proteoform atlas of bulls with low (LF; n = 6 ) and high (HF; n = 9) semen freezability. Sperm and seminal plasma proteins were fractionated by tandem size exclusion chromatography (< 30 kDa) and analyzed by mass spectrometry (operated in protein intact mode). We characterized 299 and 267 bull SP and sperm proteoforms, respectively; most of them, truncated. Interestingly, the two proteins that presented the greatest number of proteoforms play opposite roles in the regulation of calcium intake, the c-type natriuretic peptide and the caltrin. A truncated proteoform of beta-defensin 10 with pyrrolidone carboxylic acid in the N-terminal was exclusively identified in the SP of HF bulls and may be further investigated to be pointed out as a potential biomarker. Eight truncations of OPN, including one with a serine phosphorylation site, were uniquely expressed in the SP of LF bulls. Regarding sperm proteoforms, we described the acetylation of histone H2A type 1 and c-Myc protein binding proteoform in LF sires, which may indicate a deficiency in DNA packing and/or nuclear activity. This first sperm and seminal plasma proteoform atlas of any species, showed that post-translational processing appears to define bio-attributes of proteins and their empirical associations with sperm cryoresistance. Keywords: Bull. Fertility. Seminal plasma. Proteins. Proteoforms. Systematic review. Meta- analysis.